Molecular cloning, characterization, and elicitation of acetyl-CoA carboxylase from alfalfa. - Shorrosh, B S (1994)
Acetyl-CoA carboxylase [ACCase; acetyl-CoA:carbon-dioxide ligase (ADP-forming), EC 6.4.1.2] catalyzes the ATP-dependent carboxylation of acetyl CoA to produce malonyl CoA. In plants, malonyl CoA is needed for plastid localized fatty acid biosynthesis and for a variety of pathways in the cytoplasm including flavonoid biosynthesis. We have determined the full nucleotide sequence of an ACCase from alfalfa, which appears to represent a cytoplasmic isozyme. Partial cDNAs were isolated from a cDNA library of suspension culture cells that had been elicited for isoflavonoid phytoalexin synthesis. The full-length sequence was obtained by primer extension and amplification of the cDNA with synthetic primers. The sequence codes for a protein of 2257 amino acids with a calculated M(r) of 252,039. The biotin carboxylase, biotin carboxyl carrier protein, and carboxyltransferase domains, respectively, show approximately 72%, 50%, and 65% sequence similarity to those of animal, diatom, and yeast ACCase sequences. ACCase enzyme activity and transcripts are induced severalfold upon addition of yeast or fungal elicitors to alfalfa cell cultures.